Experience and Quality of Life of Health Workers Infected with COVID-19 in Gunung Sitoli - John Handy Mendrofa; Ermi Girsang; Sri Lestari Ramadhani Nasution; Chrismis Novalinda Ginting (Universitas Aisyah Pringsewu, 2022)
The task of handling and caring for people infected with COVID-19 places the position of health workers in a high-risk group. Health workers not only face physical problems when infected, the mental burden due to fears of infecting family members while doing self-isolation, and the negative stigma that develops in the community. This research is a qualitative descriptive study using a phenomenological study design. The phenomenon studied is about the experience and quality of life of health workers infected with COVID-19 in Gunungsitoli City. The study was conducted from April to May 2021. In collecting data, researchers interviewed 10 health workers consisting of 2 doctors and 8 nurses. The processed data are displayed in narrative text. The results showed that infected health workers experienced stress and physical disorders such as fever, difficulty breathing, tired easily to digestive disorders that hindered physical activity and social interaction with family members. In this study, the role of psychological support from family and co-workers is quite important in improving the health status of patients who are self-isolating. Given the negative stigma toward patients and health workers infected with COVID-19, efforts to overcome the negative stigma require collaboration from the government, mass media, and religious leaders as well as community leaders. Abstrak: Tugas penanganan dan perawatan orang yang terinfeksi COVID-19 menempatkan posisi petugas kesehatan dalam kelompok beresiko tinggi. Petugas kesehatan tidak hanya menghadapi gangguan fisik ketika terinfeksi, beban mental akibat kekhawatiran menulari anggota keluarga saat melakukan isolasi mandiri dan stigma negatif yang berkembang di masyarakat. Penelitian ini merupakan penelitian deskriptif kualitatif dengan menggunakan desain studi fenomenologi. Adapun fenomena yang diteliti adalah mengenai pengalaman dan kualitas hidup tenaga kesehatan yang terinfeksi COVID-19 di Kota Gunungsitoli. Penelitian dilaksanakan pada bulan April hingga Mei 2021. Dalam pengumpulan data, peneliti mewawancarai sebanyak 10 orang tenaga kesehatan yang terdiri dari 2 dokter dan 8 perawat. Data yang telah diolah ditampilkan dalam teks naratif. Hasil penelitian menunjukkan tenaga kesehatan yang terinfeksi mengalami stress dan gangguan fisik seperti demam, susah nafas, mudah lelah hingga gangguan pencernaan menghambat aktivitas fisik dan interaksi sosial dengan anggota keluarga. Dalam studi ini, peran dukungan psikis dari keluarga dan rekan kerja cukup penting dalam perbaikan status kesehatan pasien yang isolasi mandiri. Mengingat stigma negatif terhadap pasien dan tenaga kesehatan yang terinfeksi COVID-19, upaya untuk mengatasi hal tersebut memerlukan kolaborasi pemerintah, media massa dan tokoh agama serta tokoh masyarakat.